Semiotyka a literatura i literaturoznawstwo - Hübner, Irena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2005)
The paper concerns semiotic investigations of literature. Semiotics has always inspired literary studies. Scholars of Peirce’s school of semiotic studies attempted to answer the question whether literary text is a sign and what is its place in Pierce’s classification of signs. School based on structural linguistics (F. de Saussure's influence) has worked out two still developed approaches in semiotic studies. The former attempts to describe literature as one from the midst of semiotic systems (shaped in the same way as the natural languages), systems which can generate texts, utterances, texts of culture. The latter tries to present literary work as a sign which has its own referential abilities, abilities which are independent of reference of language.